2020
DOI: 10.1161/jaha.119.012063
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Low‐Density Lipoprotein Receptor in the Pathogenesis of Pulmonary Hypertension

Abstract: Background Recently, we and others have reported a causal role for oxidized lipids in the pathogenesis of pulmonary hypertension ( PH ). However, the role of low‐density lipoprotein receptor ( LDL ‐R) in PH is not known. Methods and Results We examined the role of LDL ‐R in the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
4
23
1
Order By: Relevance
“…Recently, Umar et al reported that a western diet increased in ammation in the lungs, and led to the development of pulmonary hypertension in LDL receptor knockout mice [22]. In the present study, although in ammatory changes were not examined, TUNEL-positive cells in pulmonary artery smooth muscle cells and caspase-3 activity in the lung were decreased in the HFD group.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Recently, Umar et al reported that a western diet increased in ammation in the lungs, and led to the development of pulmonary hypertension in LDL receptor knockout mice [22]. In the present study, although in ammatory changes were not examined, TUNEL-positive cells in pulmonary artery smooth muscle cells and caspase-3 activity in the lung were decreased in the HFD group.…”
Section: Discussioncontrasting
confidence: 57%
“…In the present study, although in ammatory changes were not examined, TUNEL-positive cells in pulmonary artery smooth muscle cells and caspase-3 activity in the lung were decreased in the HFD group. Since the role of native or oxidized LDL for apoptosis or proliferation of smooth muscle cells is controversial [22][23][24][25][26], further study is needed. In this study, the HFD group presented higher RVSP and higher HDL-C levels than the ND group; however, previous studies have shown an association of higher plasma HDL-C levels with good prognosis in human PAH [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Umar et al reported that a western diet increased the lung inflammation, leading to the development of PH in LDL receptor-knockout mice [ 22 ]. In this study, although inflammatory changes were not examined, TUNEL-positive cells in pulmonary artery smooth muscle cells and lung caspase-3 activity were more decreased in the HFD group than in the ND group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, although inflammatory changes were not examined, TUNEL-positive cells in pulmonary artery smooth muscle cells and lung caspase-3 activity were more decreased in the HFD group than in the ND group. Since the role of native or oxidized LDL for smooth muscle cell apoptosis or proliferation is controversial [ 22 26 ], further studies are needed.…”
Section: Discussionmentioning
confidence: 99%